Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pada PT Bank Tabungan Negara (Persero) Tbk Periode 2017-2021 - Nurqalby, Azzahrah; Haeruddin, M. Ikhwan Maulana; Nurman; Sahabuddin, Romansyah; Burhanuddin (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine the financial performance of PT Bank Tabungan Negara Tbk based on liquidity ratios, solvency ratios, and profitability ratios in the financial statements for the period 2017-2021. This type of research is qualitative. The population of this study is the financial statements of PT Bank Tabungan Negara Tbk for the 2017-2021 period. And the sample in this study is the balance sheet and income statement of PT Bank Tabungan Negara Tbk for the 2017-2021 period. Data collection techniques were carried out by documentation and literature studies by obtaining archival documents, journals, books, as well as professional insights that had insight into the research topic. In this study, the authors used a quantitative descriptive technique using existing ratios with certain formulas. The results of this study show a decrease in financial ratios such as quick ratios and cash ratios which indicate problems within the company or bank. A stable DER indicates that the bank relies on the use of debt to finance its operations, and there are fluctuations in ROA and ROE indicating the challenges and opportunities faced by the company.